2009
DOI: 10.1165/rcmb.2008-0211oc
|View full text |Cite
|
Sign up to set email alerts
|

The Pro-Fibrotic Factor IGFBP-5 Induces Lung Fibroblast and Mononuclear Cell Migration

Abstract: We have previously shown that insulin-like growth factor-binding protein-5 (IGFBP-5) is overexpressed in fibrotic lung tissues and that it induces production of extracellular matrix components such as collagen and fibronectin both in vitro and in vivo. We recently observed mononuclear cell infiltration in lung tissues of mice expressing IGFBP-5. We therefore examined the role of IGFBP-5 on the migration of immune cells. Migration assays demonstrated that IGFBP-5 induced migration of peripheral blood mononuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 50 publications
1
50
0
Order By: Relevance
“…Our results definitively identify 5 of 9 disulfide bonds in the protein, and determine that the other 4 linkages involve the four cysteines within the conserved GCGCCMTC motif (residues [32][33][34][35][36][37][38][39] in the N-terminal region of the protein.…”
mentioning
confidence: 56%
“…Our results definitively identify 5 of 9 disulfide bonds in the protein, and determine that the other 4 linkages involve the four cysteines within the conserved GCGCCMTC motif (residues [32][33][34][35][36][37][38][39] in the N-terminal region of the protein.…”
mentioning
confidence: 56%
“…36 The role of MAPK activation as a mediator of IGFBP-5 effects is also supported by our recent findings demonstrating that IGFBP-5 triggers the migration of peripheral blood mononuclear cells in an IGF-I-independent MAPK-dependent manner. 37 Collectively, these observations suggest that the MAPK pathway is a convergent pathway for multiple mediators of fibrosis, including IGFBP-5.…”
Section: Discussionmentioning
confidence: 97%
“…We have recently reported IGFBP-5's chemoattractant activity for human peripheral blood mononuclear cells. 19,37 IGFBP-5 has also been shown to induce migration of mouse embryonic cells, 52 porcine vascular smooth muscle cells, 21 and rat glomerular mesengial cells. 53 We and others have shown that activation of MAPK and c-Raf also plays an important role in the regulation of cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…This would not be anticipated if they were both acting by inhibiting the actions of IGFs. ERK activation by IGFBP-5 has been described and p38MAPK-dependent actions of IGFBP-5 and the ability of IGFBP-5 to activate p44/p42MAPK (Yasuoka et al, 2009b) have also been reported. It is also still a matter of debate as to whether IGFBPs exert intracellular actions, including within the nucleus.…”
Section: Ii) Direct Effects Of Igfbpsmentioning
confidence: 99%
“…Increased IGFBP-5 expression is associated with poor outcome during mammary metastasis (Huynh, 1998, McGuire et al, 1994, Mita et al, 2007, Pekonen et al, 1992. IGFBP-5 also stimulates lung, dermal and hepatic fibroblasts, inducing fibrotic responses similar to those of TGFb1 (Pilewski et al, 2005, Yasuoka et al, 2009a, Yasuoka et al, 2006a, Yasuoka et al, 2009b, Yasuoka et al, 2006b). This was somewhat surprising given that, at high concentrations, IGFBP-5 is apoptotic in mammary epithelial cells in vitro and in vivo (Marshman et al, 2003, Tonner et al, 2002 and is the IGFBP which increases dramatically during involution of the mammary gland (Clarkson andWatson, 2003, Stein et al, 2004) Consistent with an apoptotic function, two recent studies have shown that decreased expression of IGFBP-5 is associated with increased tumourigenesis in osteosarcoma (Su et al, 2011) and in breast cancer induced by foetal alcohol exposure (Polanco et al, 2010).…”
Section: Igfbps and Stromamentioning
confidence: 99%